A Study on the Correlations among Organizational Learning, Dynamic Capabilities, and Innovation Performance of Innovative Firms - Yanli Li; Xiaohan Wang (Discrete Dynamics in Nature and Society)
Innovation is the core of China’s national policy and the lifeline of enterprises at the local and global market. There has been a huge amount of research on innovation and elements contributing to innovation performance; however, few of them built a theoretical model to study the correlations among organizational learning, dynamic capabilities, and innovation performance. Based on the existing studies and literature at home and abroad and considering the development status of innovative enterprises in China, this paper decomposes organizational learning into three dimensions of learning commitment, shared vision, and open-mindedness and divides dynamic capabilities into three dimensions of environmental insight capability, resource integration capability, and organizational flexibility capability. To verify the model of LDP (learning-capability-performance) and hypotheses, the authors conducted a survey in Beijing, Tianjin, Hebei, Shanghai, and Qingdao, which have ranked top in the number of innovative enterprises in China in recent years. A sample of 232 valid questionnaires were collected and validated with SPSS23.0 software. The result shows that organizational learning and its three dimensions have significant positive effects on innovation performance, while only two dimensions of dynamic capabilities, resource integration capability and organizational flexibility capability, have significant positive effects on innovation performance. The third dimension of environmental insight capability has no significant positive effects on innovation performance. The dynamic capabilities and its three dimensions play a partial intermediary role between organizational learning and innovation performance.